Peran Online Customer Review, Online Customer Rating, dan Citra Merek pada Keputusan Pembelian - Neda Alifia Rahma; Ari Anggarani Winadi Prasetyoning Tyas (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the effect of online customer review variables, online customer ratings, and brand image on purchasing decision variables partially or simultaneously. The method used in this study is a quantitative method with a sampling method, namely non-probability sampling and the technique used is purposive sampling. The sample of this study were consumers of Mie Gacoan Cipondoh with the criteria of being at least 17 years old, having seen reviews and ratings of Mie Gacoan Cipondoh on Google Reviews, having purchased Mie Gacoan at least once in the last 3 months, and having tasted Mie Gacoan Cipondoh products. The questionnaire collected was 105 respondents, the data was then processed using multiple linear regression methods with statistical software tools. Based on the results of the analysis, it is found that online customer reviews have a positive effect on purchasing decisions. Furthermore, online customer rating has a positive effect on purchasing decisions. Then, it is also found that brand image has a positive effect on purchasing decisions. The final finding is that variables of online customer review, online customer rating, and brand image jointly influence purchasing decisions. It can be concluded that online customer reviews, online customer ratings, and brand image have an effect on purchasing decision variables partially or simultaneously.